Quality management in higher education: The individual work of students’ quality management - Gubarenko, Olena (Journal of Education Culture and Society, 2020)
The importance of this article is dictated by the necessity to adopt the Bologna standard of higher education including the module system into the frame of the Ukrainian university network. The author gives a brief review of the development of the quality concept and approaches, which have been made to integrate it into higher education management. The article sets out the new scheme of individual work of student management seen as part of the general management process.